Perfil clínico e epidemiológico dos pacientes atendidos em um ambulatório de oftalmologia em Vila Velha/ES (Brazilian Journal of Health Research, 2019)
Clinical and epidemiological profile of patients assisted in an ophthalmologic ambulatory in Vila Velha/ES, Brazil